Force Measurement of Robotic Arm for Electrode Pasting Application - Rima, Cornielyn Floricca; Low, Cheng Yee; Mustafa, Muhamad Akmal Alafifuddin (Research Progress in Mechanical and Manufacturing Engineering, 2023)
Robotic application has been globally increasing for the past decade because robots are able to perform task faster, more precise and longer with high efficiency than human. However, recent development advance in robotics especially in industrial field, have highlighted the implementation of robotic arm in various application. For instance, TDK Electronic SDN BHD suggest to apply pasting operation process using UR 10 robot. This application by UR 10 is not common and never been done before in any industry yet. Thus, this project aims are to investigate force measurement of the robotic arm to determine whether it is suitable for pasting operation by using Braccio TinkerKit robot as a prototype before real implementation on real industrial robot. Both UR 10 and tinker kit robot arm has six Degree of Freedom (DOF); for UR 10 is consist of Base, Shoulder, Elbow, Wrist 1, Wrist 2 and Wrist 3. While for TinkerKit it consists of Base, Shoulder, Elbow, Wrist Vertical, Wrist Rotation and end effector (Gripper). The movement of the TinkerKit robotic arm is depending on the rotation of the servo motor that will be programmed by Arduino Integrated Development Environment (IDE), the microcontroller of this project. This program will calibrate the robot arm for force measurement at three different positions. The results obtained with proper analysis is to determine the force performance of robotic at different joint. The findings of this study are expected to benefit both industries sector and education sector.